2014
DOI: 10.1177/0969141314522992
|View full text |Cite
|
Sign up to set email alerts
|

Community-based newborn hearing screening programme for early detection of permanent hearing loss in Iran: An eight-year cross-sectional study from 2005 to 2012

Abstract: The study results suggest that the prevalence of hearing impairment in infants in Iran is comparable with that in developed and developing countries, and that the series TEOAEs/AABRs method used in the screening programme in Iran is efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…as well as other recent publications. [ 9 14 15 16 17 ] While our newborn pass rate of 56.7% reflects a lower than average pass rate, there are numerous factors that explain this. First, 63.3% of the newborn infants screened in this study were <24 h old, which is shown to be associated with a lower pass rate.…”
Section: Discussionmentioning
confidence: 93%
“…as well as other recent publications. [ 9 14 15 16 17 ] While our newborn pass rate of 56.7% reflects a lower than average pass rate, there are numerous factors that explain this. First, 63.3% of the newborn infants screened in this study were <24 h old, which is shown to be associated with a lower pass rate.…”
Section: Discussionmentioning
confidence: 93%
“…If it were not for the support of the WOŚP foundation, the introduction of a universal hearing screening program for Polish newborns, which had been planned by the Ministry of Health prior to 2001, would probably have been delayed or the Program would not have included the entire population of Polish-born neonates [7] In the latter case, the Program could not have been referred to as universal. In the former case, a multi-stage, prolonged introduction of the Program could have led to differences in the quality of hearing screening tests, not least due to an inadequate level of personnel training.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing impairment, which is detected on average in 3 out of 1,000 newborns [5,6,7,8], should be dealt with within the healthcare system. If undetected in the early stages of a child's development, hearing impairment causes delayed speech and language skills, which may lead to cognitive challenges and pose learning problems during school education; it also disturbs the normal course of the child's development and poses many challenges for the child's parents and others.…”
Section: Introductionmentioning
confidence: 99%
“…1 This rate is reported to be 3 per 1000 among Iranian infants. 2 Approximately half a billion people affected by disabling hearing impairment which makes up about 6.8% of the world's population. These numbers are substantially very high and point to the growing importance of hearing impairment and global hearing health care.…”
Section: Introductionmentioning
confidence: 99%